Resurrection of the earthworm species Dendrobaena fedtschenkoi (Michaelsen, 1900), a former synonym of Dendrobaena byblica (Rosa, 1893) (Clitellata: Megadrili) - Szederjesi, Tímea; Latif, Robabeh; Márton, Orsolya; Csuzdi, Csaba (Zootaxa, 2018)
Dendrobaena byblica (Rosa, 1893) is a Circum-Mediterranean earthworm species complex containing more than a dozen synonymous names. From these, only two species have been resurrected so far, D. ganglbaueri (Rosa, 1894) and Fitzingeria annectens (Rosa, 1895). Here we demonstrate that Dendrobaena fedtschenkoi (Michaelsen, 1900) described from the Pamir Mts. Tajikistan differs from D. byblica both in morphological and molecular features, and represents an independent species.